Literasi dan Inklusi: Keuangan Syariah sebagai Fundamental Kesejahteraan UMKM: Edukasi Bisnis Akses Keuangan Syariah untuk UMKM Santri di Yogyakarta - Endang Sutarsih (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
In the current era of economic globalization, Financial Literacy and Inclusion are important aspects to encourage the growth and prosperity of Micro, Small and Medium Enterprises (MSMEs). Sharia finance, with its principles based on justice and mutual prosperity, is considered one of the fundamental pillars for achieving the prosperity of MSMEs. This research focuses on business education on sharia financial access for MSMEs managed by santri in Yogyakarta. Through qualitative methods, this research explores how students understand and access MSMEs to sharia finance and its impact on business growth. The research results show that although student MSMEs have a strong interest in sharia principles, there are still obstacles in literacy and access to sharia financial institutions. Special education and training on sharia finance, as well as collaboration between sharia financial institutions and Islamic boarding schools, can be a solution to increase the inclusion and welfare of student MSMEs in Yogyakarta. Efforts to improve sharia finance are expected to strengthen the fundamentals of empowering MSMEs to achieve prosperity and economic independence. This can be seen from several things: First, achieving sustainable financial prosperity. Second, financial empowerment uses product/service benefits to create economic opportunities. Third, financial inclusion is able to access needed financial products/services. Fourth, financial literacy is able to understand rights and obligations.